Біологічні, морфометричні та декоративні особливості рослин нового для України виду Syringa faurieri Lev. та методи їх використання в озелененні - Gorb, V.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective – to study morphometrical, biological and decorative features of plants of new for Ukraine species of lilac Syringa faurieri Lev. and methods of their use in landscape design. Material and methods. The objects of the study were S. faurieri plants introduced by using seeds from China. The study was performed in 2010–2018 in the Lilac garden of M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Morphological, field and analytical methods were used. Results. The botanical description of S. faurieri plants was carried out for the first time. Also for the first time the plant phenophases are described, as well as the frostresistance and the effect of the soil moisture are studied. The characteristics of the canopy formation of the stamb (grafted to trunk) plants are described. The methods of this species seed propagation and its use in landscape design are reported. Conclusions. It is revealed that S. faurieri can be successfully cultivated in the Polissya and Forest-Steppe of Ukraine. This species is recommended for the introduction in the planting of greenery for towns and villages of the Crimea and the Steppe zone of Ukraine in general due to the successful use of the closelyrelated to S. faurieri species S. amurensis Rupr. and S. pekinensis Rupr. All these species require multiple soil moistening during summer in conditions of the Crimea and the Steppe zone of Ukraine. Older (10–15years old) plants, which root system deeply entered the soil, usually do not require this procedure.